Water-based positive electrode adhesive, preparation method thereof, positive plate and lithium ion battery

By using aqueous positive electrode adhesive, the problem of poor performance of traditional PVDF and NMP systems in lithium-ion batteries is solved, and the electrochemical and safety performance of lithium-ion batteries is improved, reducing dependence on fossil energy.

CN119875546APending Publication Date: 2025-04-25GUANGDONG LIWANG NEW ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077176.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The polyvinylidene fluoride (PVDF) positive electrode bonding material used in existing lithium-ion batteries is poor in performance in high-energy density electrode materials, and the use of N-methyl-2-pyrrolidone (NMP) flammable volatile organic solvents, resulting in increased battery post-processing difficulties, desquamation of electrode particles and capacity attenuation.

Method used

An aqueous positive electrode adhesive is used, which consists of methyl methacrylate, butyl acrylate, isoocrylate, blocked isocyanate monomer, and dextran as the main raw materials, and sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether as emulsifiers. It is prepared by emulsion polymerization method to form a three-dimensional network polyacrylate-glucan system.

Benefits of technology

This aqueous positive electrode adhesive has good electrochemical properties, charge and discharge cycle performance and safety performance. It can replace the traditional PVDF and NMP binder system, improve the cycle performance and rate performance of lithium-ion batteries, reduce dependence on fossil energy, and improve resource utilization efficiency and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005247439520000011
    Figure HDA0005247439520000011
  • Figure HDA0005247439520000012
    Figure HDA0005247439520000012
  • Figure HDA0005247439520000021
    Figure HDA0005247439520000021
Patent Text Reader

Abstract

The invention provides a water-based positive electrode adhesive, a preparation method thereof, a positive plate and a lithium ion battery. The preparation method of the aqueous positive electrode binder provided by the invention comprises the following steps: A) mixing SDS, AEO-9, water, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, a blocked isocyanate group monomer and n-dodecyl mercaptan to obtain a pre-emulsion; and B) mixing the pre-emulsion with an initiator and glucan for reaction to obtain the polyacrylate-glucan adhesive. The water-based positive electrode adhesive disclosed by the invention has excellent heat resistance and flexibility, and compared with a conventional adhesive, the water-based positive electrode adhesive disclosed by the invention has relatively low electrochemical impedance and relatively high capacity and cycle capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to an aqueous positive electrode adhesive and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] With the large-scale exploitation and use of fossil energy such as oil, the problems of energy depletion and environmental pollution are becoming increasingly acute. Developing renewable energy, innovating power batteries and efficient energy storage systems, and reducing the use of fossil energy are of great significance to improving resource utilization efficiency, solving the energy crisis and protecting the environment.

[0003] Lithium-ion batteries (LIBs) have relatively high operating voltages, large specific energy, specific power, and long cycle life. They are also widely used due to their small size, light weight, low self-discharge rate, no memory effect, and no pollution. Polyvinylidene fluoride (PVDF) is used as the main positive electrode binder for the preparation of lithium-ion batteries. However, PVDF performs poorly when used as an electrode material with high energy density, and the use of flammable volatile organic solvents such as N-methyl-2-pyrrolidone (NMP) during use increases the difficulty of post-processing of lithium batteries. Studies have shown that NMP lithiated graphite reacts with lithium, resulting in the desquamation of electrode particles and battery capacity decay. Summary of the invention

[0004] In view of this, the present invention provides an aqueous positive electrode binder and a preparation method thereof, a positive electrode sheet and a lithium ion battery. The aqueous positive electrode binder provided by the present invention has good electrochemical performance, charge and discharge cycle performance and safety performance.

[0005] The present invention provides a method for preparing an aqueous positive electrode binder, comprising the following steps:

[0006] A) SDS, AEO-9, water, butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan are mixed to obtain a pre-emulsion;

[0007] B) mixing the pre-emulsion with an initiator and dextran to react to obtain a polyacrylate-dextran adhesive.

[0008] Preferably, the mass ratio of SDS to AEO-9 is 4:(7-11).

[0009] Preferably, the mass ratio of butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan is 10:(12-18):(3-5):(1.5-2.5):(0.05-0.15).

[0010] Preferably, step A) specifically comprises: dissolving SDS and AEO-9 in water, then adding butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan, stirring, and homogenizing with a homogenizer to obtain a pre-emulsion.

[0011] Preferably, the homogenization treatment is carried out at a pressure of 50 to 60 MPa and for a time of 5 to 15 min.

[0012] Preferably, in step B), the mass ratio of the dextran to the initiator is (0.5-2):10.

[0013] Preferably, in step B), the reaction temperature is 63-67° C. and the reaction time is 0.4-0.6 h.

[0014] The present invention also provides an aqueous positive electrode adhesive prepared by the preparation method described in the above technical solution.

[0015] The present invention also provides a positive electrode sheet, the preparation method of which comprises:

[0016] S1, mixing a positive electrode active material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry;

[0017] S2, coating the positive electrode slurry on a current collector, and drying to obtain a positive electrode sheet;

[0018] in,

[0019] The binder is the aqueous positive electrode binder described in the above technical solution;

[0020] The solvent is water.

[0021] The present invention also provides a lithium ion battery, wherein the positive electrode sheet is the positive electrode sheet described in the above technical solution.

[0022] The water-based positive electrode adhesive provided by the present invention is composed of methyl methacrylate (MMA), butyl acrylate (BA), isooctyl acrylate (2-EHA), blocked isocyanate monomers, and dextran as main raw materials, sodium dodecyl sulfate (SDS) and fatty alcohol polyoxyethylene ether (AEO-9) as emulsifiers, and adopts an emulsion polymerization method to prepare a three-dimensional network polyacrylate-dextran system lithium battery water-based positive electrode adhesive and lithium iron phosphate lithium battery positive electrode. The polyacrylate-dextran system lithium battery water-based positive electrode adhesive is characterized by infrared spectroscopy, differential calorimetry (DSC), and thermogravimetry, and the surface morphology of the battery positive electrode is characterized by scanning electron microscopy. The polyacrylate-dextran system lithium battery water-based positive electrode adhesive has good stability for the electrochemical performance of the battery electrode. The above-mentioned water-based positive electrode adhesive is an aqueous dispersion of a multi-copolymer, and its molecular chain segments contain carboxylate, sulfonate, hydroxyl, amine, nitrile and other functional groups, do not contain organic solvents, are safe and environmentally friendly, and give the material good bonding properties, dispersibility and film-forming properties. The aqueous positive electrode binder of the present invention can replace the traditional binder system (i.e. the system of polyvinylidene fluoride PVDF and organic solvent N-methylpyrrolidone NMP) and be used for positive electrode materials.

[0023] The test results show that the aqueous positive electrode binder of the present invention has excellent heat resistance and flexibility. Compared with conventional binders, the aqueous positive electrode binder of the present invention has lower electrochemical impedance, higher capacity and cycle capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the working principle of the aqueous positive electrode binder of the present invention;

[0026] Figure 2 is an infrared spectrum of the aqueous positive electrode binder of the present invention;

[0027] Figure 3 is a DSC curve diagram of the aqueous positive electrode binder of the present invention;

[0028] Figure 4 is a thermogravimetric analysis curve of the aqueous positive electrode binder of the present invention;

[0029] Figure 5 is a SEM image of the electrode surface of the present invention; wherein, Figure 5(a) is a SEM image of the positive electrode active material wrapped by the aqueous positive electrode binder of the present invention; Figure 5 (b) is the SEM image of the positive electrode active material wrapped with PVDF binder;

[0030] Figure 6 is a CV curve diagram of the aqueous positive electrode binder of the present invention;

[0031] Figure 7 It is the EIS curve diagram of the aqueous positive electrode binder and the PVDF binder of the present invention;

[0032] Figure 8 This is a diagram showing the effect of the cycle test of the aqueous positive electrode adhesive and the PVDF adhesive of the present invention. DETAILED DESCRIPTION

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0034] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0035] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0036] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] In this article, when referring to the units of a data range, if only the right endpoint is followed by a unit, it means that the units of the left and right endpoints are the same.

[0038] The present invention provides a method for preparing an aqueous positive electrode binder, comprising the following steps:

[0039] A) SDS, AEO-9, water, butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan are mixed to obtain a pre-emulsion;

[0040] B) mixing the pre-emulsion with an initiator and dextran to react to obtain a polyacrylate-dextran adhesive.

[0041] [About Step A]:

[0042] A) SDS, AEO-9, water, butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan are mixed to obtain a pre-emulsion.

[0043] In the present invention, the source of the SDS (sodium dodecyl sulfonate, also known as sodium dodecyl sulfate) is not particularly limited, and it can be a commercial product. In the present invention, the source of the AEO-9 (a nonionic surfactant, the Chinese name is fatty alcohol polyoxyethylene ether) is not particularly limited, and it can be a commercial product. In the present invention, the mass ratio of the SDS to AEO-9 is preferably 4: (7-11), specifically 4: 7, 4: 8, 4: 9, 4: 10, 4: 11, and more preferably 4: 9.

[0044] In the present invention, the water is preferably deionized water. In the present invention, the usage ratio of SDS to water is preferably 4g: (80-120) mL, specifically 4g: 80 mL, 4g: 90 mL, 4g: 100 mL, 4g: 110 mL, 4g: 120 mL, more preferably 4g: 100 mL.

[0045] In the present invention, the mass ratio of butyl acrylate (ie BA), isooctyl acrylate (ie 2-EHA), methyl methacrylate (ie MMA), blocked isocyanate monomer and n-dodecyl mercaptan (ie NDM) is preferably 10: (12-18): (3-5): (1.5-2.5): (0.05-0.15), more preferably 10: 15: 4: 2: 0.1. Blocked isocyanate is a type of isocyanate, which refers to a type of isocyanate whose end group is temporarily blocked by reaction and can release isocyanate groups at a certain temperature when used. In the present invention, the blocked isocyanate monomer refers to blocked isocyanate. In the present invention, the blocked isocyanate monomer is preferably an isocyanate monomer blocked by butanone oxime.

[0046] In the present invention, the mass ratio of SDS to butyl acrylate (ie, BA) is preferably 4:(8-12), specifically 4:8, 4:9, 4:10, 4:11, 4:12, and more preferably 4:10.

[0047] In the present invention, step A) preferably specifically comprises: dissolving SDS and AEO-9 in water, then adding butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan, stirring, and homogenizing with a homogenizer to obtain a pre-emulsion. After dissolving SDS and AEO-9 in water, preferably butyl acrylate is added first, stirring evenly, and then isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan are added in sequence, and each substance is fully stirred to ensure uniform mixing.

[0048] Wherein, the stirring is preferably mechanical stirring. The stirring conditions are preferably as follows: a rotation speed of 300 to 500 rpm and a time of 10 to 30 min. The homogenization treatment is preferably treated with a high-pressure homogenizer; the pressure of the homogenization treatment is preferably 50 to 60 MPa, specifically 50 MPa, 51 MPa, 52 MPa, 53 MPa, 54 MPa, 55 MPa, 56 MPa, 57 MPa, 58 MPa, 59 MPa, 60 MPa, and more preferably 55 MPa. The homogenization treatment time is preferably 5 to 15 min, specifically 5 min, 10 min, 15 min. After homogenization, a stable pre-emulsion is obtained.

[0049] [About step B]:

[0050] B) mixing the pre-emulsion with an initiator and dextran to react to obtain a polyacrylate-dextran adhesive.

[0051] In the present invention, the initiator is preferably AIBN initiator (i.e. azobisisobutyronitrile). In the present invention, the mass ratio of the initiator to butyl acrylate (i.e. BA) in step A) is preferably (0.5-1):10, specifically 0.5:10, 0.6:10, 0.7:10, 0.8:10, 0.9:10, 1:10.

[0052] In the present invention, the mass ratio of the dextran to the initiator is preferably (0.5-2):10, specifically 0.5:10, 1.0:10, 1.5:10, 2.0:10, and more preferably 1.0:10.

[0053] In the present invention, the reaction is preferably carried out in a protective atmosphere. The type of the protective atmosphere is not particularly limited, and it can be any conventional protective atmosphere in the art, such as nitrogen, argon, etc., more preferably a nitrogen atmosphere.

[0054] In the present invention, the reaction temperature is preferably 63-67° C., specifically 63° C., 64° C., 65° C., 66° C., 67° C., and more preferably 65° C. The reaction time is preferably 0.4-0.6 h, specifically 0.4 h, 0.5 h, 0.6 h, and more preferably 0.5 h. After the reaction, a milky white uniform polyacrylate-dextran binder is obtained.

[0055] The present invention also provides an aqueous positive electrode adhesive prepared by the preparation method described in the above technical solution.

[0056] The present invention also provides a positive electrode slurry, comprising: a positive electrode active material, a conductive agent, a binder and a solvent.

[0057] in:

[0058] The positive electrode active material is preferably lithium iron phosphate, that is, the corresponding lithium battery is a lithium iron phosphate lithium battery.

[0059] There is no particular limitation on the type of the conductive agent, which may be any conventional active material in the field of lithium-ion batteries; in some embodiments of the present invention, it is acetylene black.

[0060] The binder is the aqueous positive electrode binder described in the above technical solution.

[0061] There is no particular limitation on the usage ratio of the positive electrode active material, the conductive agent, and the binder, and any conventional ratio in the art may be used, preferably 20:(0.2-0.4):(0.5-1.5), and in some embodiments 20:0.3:1.

[0062] The solvent is preferably water, more preferably deionized water. The amount of the solvent is not particularly limited, and the slurry can be prepared according to the conventional amount used in preparing positive electrode slurry in the art.

[0063] The water-based positive electrode adhesive provided by the present invention is composed of methyl methacrylate (MMA), butyl acrylate (BA), isooctyl acrylate (2-EHA), blocked isocyanate monomers, and dextran as main raw materials, sodium dodecyl sulfate (SDS) and fatty alcohol polyoxyethylene ether (AEO-9) as emulsifiers, and adopts an emulsion polymerization method to prepare a three-dimensional network polyacrylate-dextran system lithium battery water-based positive electrode adhesive and lithium iron phosphate lithium battery positive electrode. The polyacrylate-dextran system lithium battery water-based positive electrode adhesive is characterized by infrared spectroscopy, differential calorimetry (DSC), and thermogravimetry, and the surface morphology of the battery positive electrode is characterized by scanning electron microscopy. The polyacrylate-dextran system lithium battery water-based positive electrode adhesive has good stability for the electrochemical performance of the battery electrode. The above-mentioned water-based positive electrode adhesive is an aqueous dispersion of a multi-copolymer, and its molecular chain segments contain carboxylate, sulfonate, hydroxyl, amine, nitrile and other functional groups, do not contain organic solvents, are safe and environmentally friendly, and give the material good bonding properties, dispersibility and film-forming properties. The aqueous positive electrode binder of the present invention can replace the traditional binder system (i.e. the system of polyvinylidene fluoride PVDF and organic solvent N-methylpyrrolidone NMP) and be used for positive electrode materials.

[0064] The present invention also provides a positive electrode sheet, wherein the binder is the aqueous positive electrode adhesive described in the above technical solution.

[0065] The present invention also provides a positive electrode sheet, the preparation method of which comprises:

[0066] S1, mixing a positive electrode active material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry;

[0067] S2, coating the positive electrode slurry on a current collector, and drying to obtain a positive electrode sheet;

[0068] Wherein, the adhesive is the aqueous positive electrode adhesive described in the above technical solution.

[0069] Regarding step S1:

[0070] The types and amounts of the positive electrode active material, conductive agent, adhesive and solvent are consistent with those described in the previous technical solution and will not be described in detail here.

[0071] Regarding step S2:

[0072] The current collector is preferably aluminum foil. The drying is preferably vacuum drying. The drying temperature is preferably 115 to 125°C, more preferably 120°C. The drying time is preferably 1.5 to 2.5 hours, more preferably 2 hours. After the above drying, it is preferably pressed using a powder tablet press. The pressing pressure is preferably 6 to 10 MPa, more preferably 8 MPa. After pressing, a positive electrode sheet is obtained.

[0073] The present invention also provides a lithium ion battery, wherein the positive electrode sheet is the positive electrode sheet described in the above technical solution.

[0074] The working principle of the aqueous positive electrode binder of the present invention is as follows Figure 1 described.

[0075] The polyacrylate-dextran aqueous positive electrode adhesive prepared by the present invention is a new type of lithium battery adhesive, and its three-dimensional structure ensures that it has excellent mechanical properties; its glass transition temperature is -25°C, and weight loss mainly occurs in the range of 300°C-418°C, indicating its excellent flexibility and thermal stability; the carboxyl group in the polyacrylate-dextran structure promotes the conduction of electrons and ions in the electrolyte and the electrode; the electrode material can be evenly distributed on its surface, improving the charge transfer process of the SEI film. In summary, the polyacrylate-dextran adhesive of the present invention is a lithium battery adhesive with excellent performance and has broad application prospects in the lithium battery industry.

[0076] The use of water-based positive electrode adhesive in the present invention can effectively replace traditional binders and organic solvents, improve production efficiency, reduce the use of fossil energy, improve resource utilization efficiency, solve energy crises and protect the environment. Water is used as a medium, which has good environmental friendliness and safety; the prepared pole piece has good adhesion and flexibility, which meets the winding processing technology; good dispersion performance and slurry stability; it can be mixed with positive electrode materials, conductive agents, etc. to prepare a uniform slurry; the battery capacity prepared by it is equivalent to that of the traditional adhesive system; the prepared lithium-ion battery has good cycle performance and rate performance.

[0077] The test results show that the aqueous positive electrode binder of the present invention has excellent heat resistance and flexibility. Compared with conventional binders, the aqueous positive electrode binder of the present invention has lower electrochemical impedance, higher capacity and cycle capacity retention rate.

[0078] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0079] Example 1

[0080] 1. Preparation of aqueous positive electrode binder

[0081] A) 4 g of SDS and 9 g of AEO-9 were dissolved in 100 mL of deionized water, and then 10 g of BA, 15 g of 2-EHA, 4 g of MMA, 2 g of butanone oxime-blocked isocyanate monomer, and 0.1 g of NDM were added, and mechanical stirring (stirring at 400 rpm for 20 min) was performed, and then homogenization was performed by a high-pressure homogenizer (pressure 55 MPa, time 10 min) to obtain a stable pre-emulsion.

[0082] B) The pre-emulsion was placed in a 250 mL three-necked flask with a condenser, 1 g of initiator AIBN was added, dextran (the mass ratio of dextran to initiator was 1:10) was added at 65° C. under nitrogen protection, and stirred for 0.5 h to obtain a milky white uniform polyacrylate-dextran binder.

[0083] 2. Preparation of positive electrode

[0084] S1. Mix lithium iron phosphate, acetylene black and the above-mentioned polyacrylate-dextran binder in a mass ratio of 20:0.3:1, add appropriate amount of deionized water and mix well to obtain a positive electrode slurry.

[0085] S2. Use a scraper to evenly apply the positive electrode slurry on the surface of the aluminum foil, vacuum dry it at 60°C for 2 hours, and then use a powder tablet press to press at 8MPa to obtain a positive electrode sheet. The obtained positive electrode sheet is vacuum treated at 120°C for 2 hours and set aside.

[0086] Reference sample: The above preparation process was followed, except that PVDF was used as a binder. Other conditions were the same, to obtain a reference electrode.

[0087] 3. Assemble the battery

[0088] The above positive electrode sheet is used as the positive electrode, the lithium sheet is used as the negative electrode, and the electrolyte is 1M LiPF6 solution (solvent is V 碳酸乙烯酯 :V 碳酸甲乙酯 :V 碳酸二甲酯 =1:3:2), Celgard2400 microporous polypropylene membrane was used as the diaphragm, button cells were assembled in a glove box filled with high-purity argon, and CR2032 button cells were obtained after being packaged by a sealing machine. The assembled batteries needed to be left standing at room temperature for 12 h to allow the electrolyte to fully infiltrate the electrode before the electrochemical performance test was carried out.

[0089] 4. Testing

[0090] (4.1) Infrared spectrum

[0091] Take a small amount of the aqueous positive electrode binder obtained in Example 1 and press it with KBr, dry it in vacuum, and then perform infrared testing with a scanning range of 4000-6500cm -1 The test results are as follows: Figure 2 As shown, Figure 2 The infrared spectrum of the aqueous positive electrode binder of the present invention is shown in FIG. -1 2850cm -1 The stretching vibration peaks of -CH in methyl (-CH3) and methylene (-CH2-) appeared at 3599cm -1 The absorption peak of hydroxyl group is 1463cm -1 The peak at 2244 cm is the six-membered ring skeleton vibration peak introduced by the closed monomer. -1 The absorption peak of CN appeared at 1737cm -1 The C=O vibration absorption peak is 1165cm -1 The vibration absorption peak of COC is shown in FIG. 1 , which indicates that each monomer has polymerized to form an adhesive.

[0092] (4.2) Differential Scanning Calorimetry (DSC)

[0093] Take an appropriate amount of the aqueous positive electrode binder obtained in Example 1 and dry it at 65°C for 12 hours. Set the experimental parameters in the DSC software: heating rate of 1°C / min, starting temperature of -30°C, and ending temperature of 20°C. The test results are as follows: Figure 3 As shown, Figure 3 The DSC curve of the aqueous positive electrode binder of the present invention is shown in Figure 1. It can be seen that a phase transition point appears at -25°C, which is the glass transition temperature of the polymer. Another phase transition point appears at 0°C, which is presumably due to the precipitation of isocyanate blocked by butanone oxime in the polymer.

[0094] (4.3) Thermogravimetric analysis (TG / DTG)

[0095] Take an appropriate amount of the aqueous positive electrode binder obtained in Example 1 and dry it at 65°C for 12 hours. Set the experimental parameters in the TGA software: heating rate of 8°C / min, starting temperature of 30°C, and ending temperature of 660°C. The test results are as follows: Figure 4 As shown, Figure 4 This is a thermogravimetric analysis curve of the aqueous positive electrode binder of the present invention. It can be seen that when the binder temperature is 100°C, the weight loss is 6%, which is presumed to be the precipitation of crystal water; at 300°C, the weight loss is 11%, mainly due to the volatilization of a small amount of light components, and the polymer itself is not decomposed. The weight loss mainly occurs in the range of 300°C-418°C, and it is presumed that the CC bond begins to break at this temperature. This figure shows that the polyacrylate-dextran system binder has good heat resistance.

[0096] (4.4) Scanning electron microscopy (SEM) characterization

[0097] The electrode surface was analyzed using a micrometer-scale scanning electron microscope with an acceleration voltage of 25KV. Figure 5 As shown, Figure 5is a SEM image of the electrode surface of the present invention; wherein, Figure 5 (a) is a SEM image of the positive electrode active material wrapped by the aqueous positive electrode binder of the present invention; Figure 5 (b) is a SEM image of the positive electrode active material wrapped by PVDF adhesive. It can be seen that the aqueous positive electrode adhesive wraps the positive electrode active material very well, and has a good wrapping effect on the positive electrode active material. The active material has good adhesion with the current collector, the pole piece is soft, and can withstand multiple winding processes. The active material is not easy to peel off, which improves the performance of the electrode.

[0098] (4.5) Cyclic voltammetry test (CV test)

[0099] The electrode was tested for cyclic voltammetry using a Solartron 1280Z electrochemical workstation with a scan rate of 8-120 Mv / s, an initial voltage of 1 V, a final voltage of 3 V, and a graphite electrode as the negative electrode of the reference cell. The test results are shown in Figure 1. Figure 6 As shown, Figure 6 The CV curve of the aqueous positive electrode binder of the present invention is shown in FIG. It can be seen that the peak spacing between the oxidation peak and the reduction peak is small, the current increase before the peak is large, and the electron transfer rate is relatively fast; the oxidation peak and the reduction peak have a symmetrical point at the equilibrium potential, and the shape is relatively regular, which can indicate that the reaction has strong reversibility in the oxidation and reduction process.

[0100] (4.6) Electrochemical impedance test (EIS test)

[0101] The electrodes were subjected to electrochemical impedance spectroscopy using a Solartron 1280Z electrochemical workstation, with a data acquisition frequency of 0.1-100kHz and an interference frequency of 5Mv. Figure 7 As shown, Figure 7 It is the EIS curve diagram of the aqueous positive electrode binder and PVDF binder of the present invention. It can be seen that both positive electrodes present a typical semicircular arc at high frequency, and the diameter of the semicircle can reflect the resistance of its conduction electrons. In the same time, the charge conduction resistance of the polyacrylate-dextran system is much smaller than that of the PVDF system. And with the storage time, the electrolyte continues to infiltrate and penetrate, the impedance of the polyacrylate-dextran system is constantly decreasing, and the impedance of the PVDF system is increasing. It is speculated that this is because the carboxyl group of the polyacrylate-dextran binder promotes the conduction of electrons and ions in the electrolyte and the electrode. Moreover, the polyacrylate-dextran binder does not swell during the charging process, which is also the reason for its low impedance.

[0102] In summary, because polyacrylate-dextran has a large number of carboxyl groups, the electrode material adheres to the current collector, ensuring that the overall structure of the electrode has good stability during multiple cycles.

[0103] (4.7) Constant current charge and discharge test

[0104] The constant current charge and discharge test of the electrode was carried out using a Solartron 1280Z electrochemical workstation. The change patterns of the points, capacitance, and capacity retention rate over time were recorded and a curve was drawn to study the battery power performance. The test results are shown in the figure below. Figure 8 As shown, Figure 8 The figure is a cycle test effect diagram of the aqueous positive electrode adhesive and PVDF adhesive of the present invention. It can be seen that at the same discharge current density, the discharge capacity and discharge voltage of the polyacrylate-dextran lithium battery are higher than those of the PVDF system. As the discharge current increases, the discharge specific volume of both decreases, but the decrease in the polyacrylate-dextran lithium battery is less than that of the PVDF system, the former decreases by 10%, and the latter decreases by 16%. It is speculated that this is because as an adhesive with superior performance, the electrode material can be evenly distributed on its surface, which to a certain extent reduces the capacity decay caused by agglomeration.

[0105] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing an aqueous positive electrode binder, characterized in that: The following steps are involved: A) SDS, AEO-9, water, butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan are mixed to obtain a pre-emulsion; B) mixing the pre-emulsion with an initiator and dextran to react to obtain a polyacrylate-dextran adhesive.

2. The preparation method according to claim 1, characterized in that: The mass ratio of SDS to AEO-9 is 4:(7-11).

3. The preparation method according to claim 1, characterized in that: The mass ratio of the butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan is 10:(12-18):(3-5):(1.5-2.5):(0.05-0.15).

4. The preparation method according to claim 1, characterized in that: Step A) specifically comprises: dissolving SDS and AEO-9 in water, then adding butyl acrylate, isooctyl acrylate, methyl methacrylate, blocked isocyanate monomer and n-dodecyl mercaptan, stirring, and homogenizing with a homogenizer to obtain a pre-emulsion.

5. The preparation method according to claim 4, characterized in that: The homogenization process is performed at a pressure of 50 to 60 MPa and for a time of 5 to 15 minutes.

6. The preparation method according to claim 1, characterized in that: In step B), the mass ratio of the dextran to the initiator is (0.5-2):

10.

7. The preparation method according to claim 1, characterized in that: In step B), the reaction temperature is 63-67° C. and the reaction time is 0.4-0.6 h.

8. An aqueous positive electrode binder prepared by the preparation method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The preparation method thereof comprises: S1, mixing a positive electrode active material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry; S2, coating the positive electrode slurry on a current collector, and drying to obtain a positive electrode sheet; in, The binder is the aqueous positive electrode binder according to claim 8; The solvent is water.

10. A lithium ion battery, characterized in that: The positive electrode sheet is the positive electrode sheet as claimed in claim 9.